Effects of Periprocedural Tirofiban vs. Oral Antiplatelet Drug Therapy on Posterior Circulation Infarction in Patients With Acute Intracranial Atherosclerosis-Related Vertebrobasilar Artery Occlusion - Sun, Xuan; Zhang, Huijun; Tong, Xu; Gao, Feng; Ma, Gaoting; Miao, Zhongrong (Frontiers in Neurology, 2020)
Background and purpose: Tirofiban and oral antiplatelet drugs can be used to inhibit reocclusion and restore microvascular reperfusion during endovascular treatment (EVT). This study compared recanalization rates, symptomatic intracranial hemorrhage (sICH), 90-day mortality, and functional outcomes between periprocedural tirofiban and antiplatelet therapy in patients with acute intracranial atherosclerosis-related vertebrobasilar artery occlusion. Methods: A total of 105 consecutive patients with acute intracranial atherosclerosis-related vertebrobasilar artery occlusion who underwent EVT + tirofiban + oral antiplatelet or EVT + oral antiplatelet therapy at the Beijing Tiantan Hospital between January 2012 and July 2018 were included. Baseline characteristics, procedural parameters, and functional outcomes were assessed. Results: Among the 105 patients, 74 underwent EVT + tirofiban + oral antiplatelet therapy, while 31 underwent EVT + oral antiplatelet drug therapy. EVT + tirofiban + oral antiplatelet therapy resulted in higher recanalization rates compared to EVT + oral antiplatelet drug therapy (93.24% versus 77.42%; p=0.038), whereas the risk for sICH, 90-day mortality, and functional independence outcomes did not differ between the groups. Logistic regression analysis revealed that EVT + tirofiban + oral antiplatelet therapy had an increased probability of higher recanalization rates (OR 0.18 [95% confidence interval (CI) 1.24–24.39]; p=0.025). There were no differences in sICH (OR 0.00 [95% CI 0.00–Inf; p=0.998), 90-day mortality (OR 1.19 [95% CI 0.17–4.05]; p=0.826) or functional independence (modified Rankin score 0 to ≤ 2) (OR 1.43 [95% CI 0.23–2.17]; p=0.538) between the groups. Conclusions: Ninety-day functional outcomes of EVT + tirofiban + oral antiplatelet therapy were not superior to those of EVT + oral antiplatelet drug therapy; however, the recanalization rate was higher and the risks for sICH and 90-day mortality were lower.